ICHTHYOLOGICAL INVENTORY AND FISHERIES PROSPECTS INRAMRO PATANG LAKE, PASIGHAT, ARUNACHAL PRADESH, INDIA - GURUMAYUM, SHANTABALA DEVI (Journal of the Inland Fisheries Society of India, 2026)
Ichthyological  inventory and  fisheries prospects in ramro patang lake, Pasighat, Arunachal Pradesh, India